A traffic perimetry test that adheres to the European visual field requirements. Issue 4 (30th September 2020) - Jørstad, Øystein Kalsnes; Jonsdottir, Thora Elisabet; Zysset, Stefan; Rowe, Fiona
Abstract: Purpose: European visual requirements for driving generally follow the standards of the European Union (EU), but the lack of a uniform perimetry algorithm leads to differing practices in enforcing visual field regulations. The purpose of this study was to develop a perimetry algorithm for group 1 driving licenses (car and motorcycle) that adheres to the European requirements. Methods: We determined the features of a traffic perimetry algorithm complying with the EU directive 2009/113/EC and the underlying scientific report by the Eyesight Working Group. The final algorithm was a binocular, supra‐threshold test with 37 central and 86 peripheral test points within 140º x 40º. It was created as a custom test for an Octopus 900 perimeter and tested on participants with known visual field defects. Findings were compared with the Esterman program in reference to British and Norwegian regulations, which both recommend the Esterman program for assessing fitness to drive but differ in definition of negative and positive results. Results: Twenty‐five participants were examined. In comparison with the traffic perimetry algorithm, sensitivity and specificity of the British regulations were 0.78 (95% confidence interval (CI) 0.40‐0.97) and 1.00 (95% CI 0.79‐1.00). Similarly, sensitivity and specificity of the Norwegian regulations were 0.89 (95% CI 0.52‐1.00) and 0.81 (95% CI 0.54‐0.96). Conclusion: The lack of a perimetry algorithm that conforms to the scientific recommendations challenges the fundamental right of European drivers for legal equality. This study demonstrates a binocular supra‐threshold test that adheres to the European visual field requirements for group 1 driving licenses.